Develop reusable and combinable designs for transcriptional logic gates - Jian Zhan; Bo Ding; Rui Ma; Xiaoyu Ma; Xiaofeng Su; Yun Zhao; Ziqing Liu; Jiarui Wu; Haiyan Liu (Molecular Systems Biology)
Abstract One limit on developing complex synthetic gene circuits is the lack of basic components such as transcriptional logic gates that can process combinatorial inputs. Here, we propose a strategy to construct such components based on reusable designs and convergent reengineering of well‐studied natural systems. We demonstrated the strategy using variants of the transcription factor (TF) LacI and operator Olac that form specifically interacting pairs. Guided by a mathematical model derived from existing quantitative knowledge, rational designs of transcriptional NAND, NOR and NOT gates have been realized. The NAND gates have been designed based on direct protein–protein interactions in coupling with DNA looping. We demonstrated that the designs are reusable: a multiplex of logic devices can be readily created using the same designs but different combinations of sequence variants. The designed logic gates are combinable to form compound circuits: a demonstration logic circuit containing all three types of designed logic gates has been synthesized, and the circuit truthfully reproduces the pre‐designed input–output logic relations.